An Interactive Educational Platform for Introducing Genetic Algorithm Concepts - Moreira, Gessyca; de Jesus, Ângelo Magno; de Paula, Suelen Mapa (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Teaching Artificial Intelligence (AI) concepts is challenging due to their abstract and interdisciplinary nature. Objective: This work presents an interactive educational platform to support the learning of Genetic Algorithms (GAs), making their processes tangible through simulations and visualizations. Methodology: The platform was developed using web technologies and evaluated with undergraduate students through the MEEGA+ model [Petri et al. 2019]. Expected Results: Results indicate that 94.4% of participants considered the tool intuitive and suitable for educational use, highlighting its strong pedagogical potential.